Assets and Barriers to Finding Employment - Stolte, Michael (Canadian Journal of Counselling and Psychotherapy, 2007)
In this intact-groups, quasi-experimental study, 115 unemployed job seekers who utilized federally funded labour market interventions were compared on program usage (long- or short-term), personality, personal meaning, employability skills, job search length, and pain and suffering. Results did not fi nd signifi cant differences in program usage or job search length, though employability skills were found to correlate positively with education level, extraversion, openness, agreeableness, conscientiousness, and personal meaning, and inversely with negative emotionality. Further analysis found those of Non-Western ethnicity had longer job search lengths and higher levels of pain and suffering while simultaneously scoring higher in meaning and employability skills.